Schlösser in Ungarn - Örsi, Károly; Dercsényi, Balázs; Himer, Christa; Koppány, Tibor; Hegyi, Gábor; Dercsényi, Balázs ([Budapest] : Verl. Officina Nova, 1990)
Das Gotische schloss - Das Renaissanceschloss - Das Barocke Schloss - Klassizistische Schlösser - Schlösser der Romantik - Das Historisierende (Eklektische) Schlösser - Acsa - Bozsok - Budapest, Nagyteteny - Bük - Csakvar - Deg - Doba - Egervar - Fertod - Hajos - Hedervar - Keszthely - Kormend - Martonvasar - Mihalyi - Nadasdlandany - Nagycenk - Noszvaj - Pacin - Papa - Pecel - Petervasara - Rackeve - Sarospatak - Sarvar - Seregelyes - Szabadkigyos - Szecseny - Szirak - Tata - Tiszadob - Vasszecseny - Zsennye - Zsira
Übers. aus dem Ungar
Keywords: Bildband